Pelatihan Sprint 3 Repetisi 3 Set Untuk Meningkatkan Kecepatan Tendangan Depan Pada UKM Pencak Silat UPG 1945 NTT - Bete, Dixon Taek; Kollo, Moses (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2019)
The purpose of this study was to study whether sprint 3 repetitions of 3 sets can increase the speed tendencies of the Pencak Silat UKM of UPG 1945 NTT. The method used in this study is the experimental method with the design of the study design is one group pretest-post test design. This research was conducted in the UKM Perisai Diri at the Pencak Silat UKM of UPG 1945 NTT. The time used in this study is 1 year. The test used is the test of doing the front kick for 1 minute to find out the speed of the front kick. The data analysis technique used is the t-test method. The results of data analysis showed the average initial test of front kick = 70.87, Final test = 78.07 and t-count = 7.059. The results of the next calculation are compared df = N-1 (15-1) = 14, then it is obtained 1.761 at the significance level of 5%, which means t-count (7.059)> t-table (1.761). Thus the Ha is accepted while the Ho is rejected, because the t-count value is greater than t-table. Based on the results of data analysis it can be concluded that sprint training 3 repetitions of 3 sets can increase the speed tend to be in the the Pencak Silat UKM of UPG 1945 NTT is 10.16%.